2014
DOI: 10.1902/jop.2013.130400
|View full text |Cite
|
Sign up to set email alerts
|

Routine Prophylaxes Every 3 Months Improves Chronic Periodontitis Status in Type 2 Diabetes

Abstract: Routine prophylaxes every 3 months significantly improve periodontal health and prevent progression of CP in both poorly controlled and well-controlled patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
6
13
0
1
Order By: Relevance
“…This observation connotes to the fact that, the average pocket depth had reduced to < 3 mm after NSPT and there by the overall surface area of the pocket lining which acts as a reservoir for periodontal pathogen and inflammatory markers had also reduced. This finding was in accordance with previous studies where significant pocket depth reduction had been observed after NSPT in non diabetic and diabetic patients[25,26]. In control group there was an increase in probing pocket depth and clinical attachment level.…”
Section: Discussionsupporting
confidence: 93%
“…This observation connotes to the fact that, the average pocket depth had reduced to < 3 mm after NSPT and there by the overall surface area of the pocket lining which acts as a reservoir for periodontal pathogen and inflammatory markers had also reduced. This finding was in accordance with previous studies where significant pocket depth reduction had been observed after NSPT in non diabetic and diabetic patients[25,26]. In control group there was an increase in probing pocket depth and clinical attachment level.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, reports from studies that investigated the treatment of periodontal disease in diabetic patients have described improvements in HbA1c levels and periodontal disease; similar improvements were seen in studies that educated patients about how to care for periodontal disease and diabetes simultaneously . On the other hand, studies like the current study, which only provided education related to caring for periodontal disease, have demonstrated improvements in periodontal disease, but no significant improvements in HbA1c levels. Similarly, our study did not show any significant improvements in HbA1c levels.…”
Section: Discussionsupporting
confidence: 68%
“…It is well known that dental prophylaxis alone plays a role in periodontal health but does not affect the improvement of HbA1c levels [38].…”
Section: Discussionmentioning
confidence: 99%